Understanding and predicting trends in adsorption energetics on monolayer transition metal dichalcogenides - Brian H. Lee; Jameela Fatheema; Deji Akinwande; Wennie Wang (npj 2D Materials and Applications)
Abstract Two-dimensional (2D) transition metal dichalcogenides (TMDs) have emerged as promising candidates for non-volatile resistive switching (NVRS) due to their atomic-scale thickness, enabling high-density integration and low energy consumption. This study explores how metal adatom adsorption and desorption modulate resistivity in these materials. By examining a range of transition-metal adsorbates on MoS2, MoSe2, WS2, and WSe2, we uncover material-specific trends in adsorption energies that correlate with electronic and atomic structure descriptors. These trends are captured by simple models that elucidate how adsorption influences the formation and dissolution of point defects, a key mechanism in NVRS. Our results highlight consistent periodic behavior across TMDs and demonstrate that adsorption energy is a useful predictor of switching energy. This understanding provides insight into atomic-scale switching phenomena and offers design principles for selecting TMD-adsorbate pairs to optimize NVRS device performance.